2019
DOI: 10.1158/2326-6066.cir-18-0613
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of High-Dose Glucocorticoids on the Outcome of Immune-Checkpoint Inhibitor–Related Thyroid Disorders

Abstract: Thyroid disorders have emerged as one of the most common immune-related adverse events (irAE), yet optimum management and biomarkers to predict vulnerable individuals remain to be explored. High-dose glucocorticoid (HDG) therapy is routinely recommended for irAEs. However, systematic analysis of the impact of glucocorticoid therapy on the outcome of immune-checkpoint inhibitor (ICI)-induced thyroid disorders is lacking. We analyzed 151 patients with or without ICI-related thyroid disorders. We divided the pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 43 publications
2
48
0
Order By: Relevance
“…ICIs can be continued in the context of thyroiditis, and most patients are simply treated with thyroid replacement. Treatment with corticosteroids has not been shown to affect the duration or degree of thyroid dysfunction 68…”
Section: Clinical Presentation Of Checkpoint Inhibitor Associated Autmentioning
confidence: 99%
“…ICIs can be continued in the context of thyroiditis, and most patients are simply treated with thyroid replacement. Treatment with corticosteroids has not been shown to affect the duration or degree of thyroid dysfunction 68…”
Section: Clinical Presentation Of Checkpoint Inhibitor Associated Autmentioning
confidence: 99%
“…These patients may present with elevated Thyroid stimulating hormone (TSH) and low levels of T4. According to a retrospective cohort study by Ma et al [ 24 ], the median time to onset of hypothyroidism in patients receiving pembrolizumab (PD-1 inhibitor) was found to be 84 d (range: 43-544; P = 0.333) . For those receiving nivolumab (PD-1 inhibitor) and ipilimumab (CTLA-4 inhibitor) + nivolumab (PD-1 inhibitor), the median time to onset was 84 d (range: 14–154; P = 0.002) and 62 d (range: 21–141; P = 0.057) respectively[ 24 ].…”
Section: Endocrinementioning
confidence: 99%
“…Furthermore, many patients may commonly be asymptomatic, with the hyperthyroid state uncovered on routine laboratory investigations[ 21 ]. Ma et al [ 24 ] found that the median time to onset of thyrotoxicosis in patients treated with pembrolizumab (PD-1 inhibitor) was 44 d (range: 19-447; P = 0.593), while time for those receiving nivolumab (PD-1 inhibitor) was 56 d (range: 13-126; P = 0.004) and ipilimumab (CTLA-4 inhibitor) + nivolumab (PD-1 inhibitor) was 21 d (range: 7-64; P = 0.158). It is abundantly evident from these studies that the use of combination therapy leads to a more rapid symptom onset.…”
Section: Endocrinementioning
confidence: 99%
“…Typically, hypothyroidism [elevated thyroid-stimulating hormone (TSH), normal or low FT4] presents with nonspecific symptoms such as fatigue, asthenia, cold intolerance, and dry skin. The management of hypothyroidism consists of thyroid hormone replacement (levothyroxine), usually starting with 0.8–1.0 µg kg −1 day −1 (Ma et al, 2019) and supportive care. ICI therapy is withheld in severe cases until symptoms resolve to baseline with appropriate supplementation.…”
Section: Common Iraes and The Relevant Management In Hnsccmentioning
confidence: 99%
“…In the most recent study of MA and colleagues, high-dose glucocorticoids (HDGs) did not improve the outcome of ICI-related thyroid disorders; therefore, routine use of HDGs in patients with suspected thyroid disorders such as thyrotoxicosis is not recommended. In addition, they suggested using HDGs in patients who present with symptoms of thyroid storm or in patients with cardiac disease (Ma et al, 2019).…”
Section: Common Iraes and The Relevant Management In Hnsccmentioning
confidence: 99%